2020
DOI: 10.35333/jrp.2020.112
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the effect of glidant on the compaction and tableting properties of paracetamol granules

Abstract: Glidants play a vital role in tablet formulation. This study aimed to examine the impact of glidants on the compaction and tableting properties of paracetamol granules prepared by wet granulation. Three formulations of paracetamol granules were prepared to consist of either talc, colloidal silicon dioxide (CSD) or a combination of both in equal proportion (1:1) as glidants added extragranularly. The granules were characterised by measuring the particle size, angle of repose, bulk and tapped densities, true den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Studies reported colloidal silicon dioxide (Aerosil®), acts both as a glidant and lubricant and also helps inappreciably decreasing tablet friability by restoring the binding properties of the excipients. [21] The hardness of the LS2 liquisolid tablets was reported to be 5.78 ± 0.018 kg/cm 2 which met the criteria as displayed in the I.P between 5 kg/cm 2 and 6 kg/cm 2 , the data reveal that the LS2 tablet is having good mechanical strength. Sufficient hardness of tablet may be due to the presence of hydrogen bond between the drug and the Avicel PH102 that contribute to strength and cohesiveness among the particles.…”
Section: Post-compression Studiesmentioning
confidence: 74%
“…Studies reported colloidal silicon dioxide (Aerosil®), acts both as a glidant and lubricant and also helps inappreciably decreasing tablet friability by restoring the binding properties of the excipients. [21] The hardness of the LS2 liquisolid tablets was reported to be 5.78 ± 0.018 kg/cm 2 which met the criteria as displayed in the I.P between 5 kg/cm 2 and 6 kg/cm 2 , the data reveal that the LS2 tablet is having good mechanical strength. Sufficient hardness of tablet may be due to the presence of hydrogen bond between the drug and the Avicel PH102 that contribute to strength and cohesiveness among the particles.…”
Section: Post-compression Studiesmentioning
confidence: 74%
“…However, every material in question, for flow modification, would need to undergo consideration for its end-to-end impact on the process. Silicates, for instance, have been shown to negatively impact compatibility [ 66 , 67 ] but also improve flowability and therefore improve feeder processing consistency [ 5 , 43 , 55 ], whereas magnesium stearate has also been shown to increase flowability, but due to its hydrophobicity—coating the surface of the API—would hinder the dissolution of the API within the formulation [ 68 ]. This would result in the material being greatly undesirable for any scenario which may involve the intimate blending, or over-mixing, of magnesium stearate with API.…”
Section: Powder Feedingmentioning
confidence: 99%
“…Additives, such as glidants (e.g., SiO ), are typically used to make the bulk powder properties easier to deal with, by increasing flowability [ 5 , 37 , 57 ]. However, additives change the overall formulation composition, which can have detrimental effects on downstream processing-namely tabletting [ 66 , 67 ]. In contrast, process changes (processing parameters) can potentially overcome issues relating to cohesion without altering the formulation’s composition [ 43 , 75 , 88 ].…”
Section: Blendingmentioning
confidence: 99%
“…The role of the glidant as an extragranular excipient is to improve the flowability of the granules (Apeji, Olowosulu, 2020). They are often added to a granulation before compression into tablets to ensure that the granules flow sufficiently from the hopper during high-speed production.…”
Section: Optimization Of the Extragranular Excipient Composition Of P...mentioning
confidence: 99%